Solar radiation can cause clinically relevant burns in breast reconstructed patients even after years- a rare case report - Till Wagner; Anne-Sophie Kruit; Marielle Vehmeijer-Heeman; Dietmar Ulrich (Elsevier, 2024)
We hereby present a rare case of a full-thickness skin burn after solar radiation by wearing a black bra. The patient underwent late 2020 a delayed bilateral autologous breast reconstruction with a bilateral DIEP flap, followed shortly after by a latissimus dorsi flap reconstruction of her left breast caused by flap necrosis of the left-sided DIEP flap and a secondary nipple reconstruction with afterward a small cosmetic correction. Shortly after she travelled for a holiday in November 2023 to Egypt. After less than 2 h sunbathing in the afternoon in her black bra, she recognized later in the evening redness and blistering of the skin of her right breast. After return and presentation to our outpatient department, we stated a 2b-3 degree burn of her right lateral breast. Under conservative treatment no progress was seen, thus we scheduled the patient for a direct resection and primary closure of the burned skin, which further healed uneventfully. This case presentation shows again the potential risk of solar burns in breast-reconstructed patients with reduced skin sensitivity even after years. Therefore patients undergoing breast reconstruction should be informed about this issue and medical professionals should be aware of this potential harm in these population groups.